Global connections : politics, exchange, and social life in world history. Volume II - Coatsworth, John H., 1940- (Cambridge University Press, 2015)
The first textbook to present world history via social history, drawing on social science methods and research. This interdisciplinary, comprehensive, and comparative textbook is authored by distinguished scholars and experienced teachers, and offers expert scholarship on global history that is ideal for undergraduate students. Volume 2 takes us from the early modern period to speculation about the world in 2050, visiting diverse civilizations, nation-states, ecologies, and people along the journey through time and place. The book pays particular attention to the ways in which ordinary people lived through the great changes of their times, and how everyday experience connects to great political events and the commercial exchanges of an interconnected world. With 75 maps, 65 illustrations, timelines, boxes, and primary source extracts, the book enables students to use historical material and social science methodologies to analyze the events of the past, present, and future.